Investigation of Telemedicine Services, An Innovative and Technology-Based Healthcare Application, by Using the Extended Technology Acceptance Model (TAM2): An Example from Turkey - Türkyılmaz, Serap (European Journal of Applied Sciences, 2023)
Today, people use the internet to meet their information and communication needs related to health. This study aims to develop an acceptance model for Telemedicine Services, which is a technology-based health application in the new world order in which we experience digital transformation, and to determine the factors affecting the intention of individuals living in Turkey to use Telemedicine services in line with the results of the study. The quantitative survey research method was used for the purpose of this study. Research data were collected from 248 participants by using the online survey method. The data were analyzed using the Partial Least Squares (PLS) method. The results revealed that perceived usefulness, self-efficacy, trust, price value, technology anxiety, and perceived risk are a function of the intention to use telemedicine services. Moreover, facilitating conditions, perceived ease of use, resistance to use, and social influence were observed to not significantly affect the behavioral intention to use such applications. In the current literature, no study has been conducted to determine the factors affecting the intention of individuals living in urban centers and rural areas in Turkey, a developing country, to adopt telemedicine applications. This study may contribute to the literature on telemedicine and the development of future telemedicine applications in the health industry in Turkey. This research confirms that the Technology Acceptance Model (TAM) can be used to model the adoption of telemedicine services in developing countries by including additional variables. The results of this study will facilitate understanding the acceptance of telemedicine services. It will not only facilitate predicting the future adoption but also developing proper solutions to address barriers to the use of telemedicine applications.